Palladium‐Catalyzed Hydroxycarbonylation of Diisobutene: Systematic Optimization by Central Composite Design. Issue 11 (28th September 2022) - Dühren, Ricarda; Kucmierczyk, Peter; Jackstell, Ralf; Franke, Robert; Beller, Matthias
Abstract: The selection of suitable catalysts and reaction conditions are key elements for efficient process development. In this work, stability studies of homogeneous palladium catalysts used for the hydroxycarbonylation of olefins to aliphatic carboxylic acids are presented. Based on this, the hydroxycarbonylation of diisobutene, which represents an industrially relevant mixture of olefins, was investigated and optimized by means of central composite design with respect to the yield of the target product 3, 5, 5‐trimethylhexanoic acid. The modeling succeeds with high accuracy and allows to gain information about interactions between different factors in the reaction system. This allows a more accurate prediction of the reaction behavior and permits easier future scale‐up of such processes. Abstract : This work addresses the optimization of palladium‐catalyzed hydroxycarbonylation of the industrial relevant olefin mixture diisobutene. Stability studies and central composite design were successfully applied to select a suitable catalyst and reaction conditions to optimize the yield of the target product 3, 5, 5‐trimethylhexanoic acid.